Enxerto ósseo autógeno mantido em diferentes meios de armazenagem no período transcirúrgico: Análise histomorfométrica em coelhos - Batista, Jonas Dantas (2007)
The success of autogenous bone graft is related to the graft cells viability transferred to receptor site. During surgical bone grafting procedures, a time passes by the graft removal till its fixation in receptor site. Various media for temporary storage of bone grafts during the surgical procedure have been suggested to minimize the deleterious effect during this period. This study performs histomorphometric analysis of autogenous bone graft, stored in different medias during surgical period. Two grafts were removed bilaterally from calvarian of 18 rabbits. One graft was removed and immediately fixed in one of the mandibular angles (control group). The other graft was stored during 30 minutes in one of the following storage media: salin solution (saline group), air (dry group), platelets poor-plasma (PPP group), and then screwed in the symmetrical side of the first graft, in the same animal. Four weeks later the animals were killed and the grafted areas were harvested and fixed in formaldehyde in PBS and embedded in parafin. The 5 μm sections were stained in Hematoxilin Eosin and Mallory. Osteoclasts, blood vessels and total graft area were assessed and analyzed through, ANOVA 1, Tukey and t-matched pair tests. Histological analysis of all groups showed vascularized, preserved bone graft well-incorporated to receptor site. Statistical analysis of saline group shows higher amount of osteoclasts (p=0,02) and lower amount of blood vessels (p=0,03) than the control group. No differences between control and experimental groups were observed in dry and PPP groups. Comparing experimental groups, PPP group presented higher amount of blood vessels (p<0,001) and larger total graft area (p<0,001) than dry and saline group. The platelets poor plasma favored the vascularization and maintenance of graft area, being considered a better storage media than air way and saline solution.